The Fund's Mandate : An Overview. (Policy Papers; Policy Paper ;, 2010)
This paper, and a companion piece on legal aspects 'The Fund's Mandate-The Legal Framework,' is the first in a series of reflections on the Fund's mandate-on what it should be doing to promote global stability and how the membership might support that process. At this stage, the aim is not to put forward concrete proposals but to float ideas with a view to stimulating a broader debate. Follow up papers, based on feedback from the Executive Board and public outreach, are planned ahead of the final report to the IMFC in September.